Pendidikan Agama Islam Di Perguruan Tinggi Umum: Studi Kasus Di Universitas Lakidende - Sastramayani Sastramayani; Sabdah Sabdah (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
Islamic Education in Higher Education is a subject spearhead the development of the personality. The hope is that students have a strong character in the practice of science, technology and art. In practice in Public Higher Education, the course is not getting treatment that is consistent with the spirit of building a formidable generation. Lakidende University also showed the same trend in which universities do not have a clear design of the position of subjects of Islamic education in the curriculum is. The response of students to the courses of Islamic education is still the same with other subjects. The measures taken by the lecturer of Islamic education are still in the context of educational interaction in the classroom, there was no movement in the form of additional activities outside of the classroom as on material enrichment classes.Keywords: Islamic Education, Public Higher Education, Curriculum